2019
DOI: 10.1016/j.brat.2019.103434
|View full text |Cite
|
Sign up to set email alerts
|

Music to my ears, goal for my eyes? Music reward modulates gaze disengagement from negative stimuli in dysphoria

Abstract: Attentional bias for negative information, i.e. difficulties in disengagement from negative stimuli, is considered to be one of the core mechanisms involved in the onset and maintenance of depression. However, current attention training procedures aimed at reducing this bias have shown limited success. In addition to the reliability and validity concerns generated by the use of dot-probe paradigm in these procedures, an important factor is the limited consideration of motivational influences in the use of atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The study of attentional biases and ABMT would benefit from identifying more reliable outcomes, novel and psychometrically validated tasks, and the use of multiple measures of attention bias to enable latent variable modeling of bias as potential ways forward. In addition, alternative approaches to modifying negative attentional bias (e.g., Godara et al, 2019;Shamai-Leshem et al, 2020) may be worth exploring as stronger empirical tests of whether modifying negative attentional bias reduces depression symptom severity over time if these methods can achieve greater target engagement than what was demonstrated in this study.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The study of attentional biases and ABMT would benefit from identifying more reliable outcomes, novel and psychometrically validated tasks, and the use of multiple measures of attention bias to enable latent variable modeling of bias as potential ways forward. In addition, alternative approaches to modifying negative attentional bias (e.g., Godara et al, 2019;Shamai-Leshem et al, 2020) may be worth exploring as stronger empirical tests of whether modifying negative attentional bias reduces depression symptom severity over time if these methods can achieve greater target engagement than what was demonstrated in this study.…”
Section: Resultsmentioning
confidence: 96%
“…In addition, alternative approaches to modifying negative attentional bias (e.g. Godara, Sanchez-Lopez, & De Raedt, 2019;Shamai-Leshem, Lazarov, Pine, & Bar-Haim, 2020) may be worth exploring as stronger empirical tests of whether modifying negative attentional bias reduces depression symptom severity over time if these methods can achieve greater target engagement than what was demonstrated in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Correspondingly, recent studies employing dysphoric individuals found that attention bias for negative stimuli, i.e. difficulty to disengage from negative material, could be modulated using music-rewarded and white noise-punished top down goals (Godara, Sanchez-Lopez, De Raedt, 2019;2021). Therefore, in the current study we used music reward and white noise punishment reinforced top-down goals to train attention towards affective stimuli in dysphoric individuals.…”
Section: Introductionmentioning
confidence: 83%
“…By manipulating the instrumentality of avoidance motivation, attention to negative information can be balanced across contexts. In a recent study it was found that rewards (music and earning money) can also be used to modulate attention away from negative stimuli in dysphoric individuals (Godara, Sanchez-Lopez, & De Raedt, 2019). Drawing on these results, future training procedures could employ both reward approach and punishment avoidance components to modulate attention in a contextual manner, in order to improve adaptive, situation-specific emotional responding.…”
Section: Discussionmentioning
confidence: 99%